The Reflection of Lean Management Approach on Human Resource Management Practices A field research in telecom companies in Iraq (Zain-Asia cell) - تناي غني دحام; جاسم رغد جمال (Journal of Economics and Administrative Sciences, 2016)
Abstract The current research is attempt to test the reflection of the lean management on the human resources management practices of two of the most important communication companies operating in Iraq (`Zain & Asia cell), The research aims to Determine the extent of adoption of the lean management approach in the two researched companies, as it improving human resource management practices. The research problem represented in the existence of lack of in some aspects of the application the lean management approach in service sector and neglecting the impact of its tools on the human resource management practices. For this purpose three principle research hypotheses has been formulated, first there is a correlation relationship refers to moral and positive guidance between the variables lean management and the human resources management practices, the second principle hypothesis refers to be impact is moral guidance for the lean management approach in human resources management practices, and the thired principle hypothesis refers to between the two researched companies the extent of adoption of the lean management approach and HRM practices, all has been tested statistically on random sample of employees in the researched companies. The two researcher concluded with a set of recommendations, the most important was the need to increase awareness and interest in the concept of lean management as a mean to improve human resources in case that both companies commitment to it